Self-efficay beliefs and the relation between career planning and perception of barriers - Cardoso, Paulo (2010)
This study tested the hypothesis that self-efficacy in career roles moderates the relation between perception of career barriers and career planning, in a study with Portuguese students, 488 in grade 9 and 517 in grade 12. The results supported the hypothesis only among grade 9 girls, showing that perception of career barriers leads to less career planning among girls low in self-efficacy. The findings suggest that variables such as gender and psychological maturity need to be considered in understanding career planning.